Cheese manufacturing wastewater treatment by combined physicochemical processes for reuse and fertilizer production. (15th June 2020) - Guerreiro, Raquel C.S.; Jerónimo, Eliana; Luz, Silvana; Pinheiro, Helena M.; Prazeres, Ana R.
Abstract: Making cheese manufacturing environmentally sustainable is a major concern in the integrated management of this industrial sector. This concern is mainly due to the environmental impact of the discharge of its wastewaters, carrying heavy loads of salinity, nutrients, organic matter, solids and oils and fats. These discharges must meet increasingly stringent quality requirements. Some physicochemical (e.g. coagulation-flocculation, precipitation, oxidation) and biological (e.g. aerobic and anaerobic bioreactors and wetlands) treatments have been studied to address this problem. However, these treatments involve costs that some producers cannot sustain, face difficulties with biological reactor operational stability and often fail to consistently produce effluents compatible with discharge standards. In this context, aiming at the design of a simple and economical treatment method, several precipitation processes were tested using a fixed dosage of CaCO3 (75 g/L), combined with different dosages of FeCl3, FeSO4 or Ca(OH)2 . The goal of the treatment was to produce a supernatant that would be evaluated as to its suitability for discharge into natural water courses or municipal treatment systems, or for reuse applications. The generated sludge would be evaluated for possible agricultural valorization. Through the measurement of the relevant supernatant quality parameters and using statistical analysis, it was possible to choose the best dosages for each of the tested coagulants (1.0, 1.0 and 0.6 g/L for FeCl3, FeSO4 and Ca(OH)2, respectively). Among these, the most efficient treatment was obtained with CaCO3 75 g/L + FeSO4 1.0 g/L. For this best-case scenario, the treatment led to removal yield values of 55.1% for chemical oxygen demand (COD), 92.0% for total phosphorus, 95.7% for turbidity, 59.1% for total phenols, 94.3% for nitrates, 71.0% for nitrites, 51.0% for total solids (TS) and 97.2% for oils and fats. The treatment did not produce an effluent supernatant with adequate quality for direct discharge into water courses, serving however as an efficient pretreatment for agricultural reuse. All the sludges generated in these treatments showed good potential for agricultural valorization due to their high nutrient content, along with pH and conductivity values within the acceptable ranges for soil application. Thus, this work contributes for a better integration of the cheese manufacturing industry in the overall aims of water and nutrient resources recovery in rural, agricultural areas. Highlights: Precipitation with calcium carbonate and calcium or iron coagulants was tested. Calcium carbonate + Iron (II) sulfate produced the best pollutant removal yields. Key pollutant load parameter values were reduced by 55–97%. Obtained sludges showed agricultural valorization potential due to nutrient content.